Transition to PCR diagnosis of cryptosporidiosis and giardiasis in the Norwegian healthcare system: could the increase in reported cases be due to higher sensitivity or a change in the testing algorithm? - Campbell, Sophie M.; Pettersen, Frank O.; Brekke, Hanne; Hanevik, Kurt; Robertson, Lucy J. (European journal of clinical microbiology & infectious diseases, 2022)
Cryptosporidiosis has been a notifiable infection in Norway since 2012 and giardiasis since 1977. For both infections, there has been an increase in notified cases. We used a questionnaire to explore whether this may be associated with implementation of molecular diagnostic methods. We received responses from 14 of 16 laboratories, most of which had implemented molecular diagnostic methods for these parasites. Algorithms for testing had also been modified, and several laboratories now test more faecal samples than previously for both parasites. The increase in reported cases may reflect not only higher sensitivity of diagnostic methods, but also more sample testing.